Seasonal features of detecting and countering criminally punishable illegal hunting - Seralina А.Ж.; Ablaeva Э.Б.; Savakassova А.Т. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2026)
The article examines the seasonal features of detecting and countering criminally punishable illegal hunting in the Republic of Kazakhstan. The relevance of the work is due to the growing public and state interest in environmental safety issues, as well as the lack of comprehensive studies in domestic criminal law and criminology on the influence of seasonal factors on the dynamics of registration of crimes under Article 337 of the Criminal Code of the Republic of Kazakhstan. The problem is that official statistics show a pronounced unevenness in the detection of illegal hunting during the year, but this pattern has not previously received a systematic scientific analysis. The purpose of the study is to identify, quantify and scientifically substantiate the influence of the seasonal factor on the dynamics of registration of criminally punishable illegal hunting, as well as to develop recommendations for improving the effectiveness of its detection and prevention. The work is based on an analysis of official statistical data for 2020-2025, including 72 calendar observations. The study uses formal legal, statistical, comparative analytical, systemic and dialectical methods, as well as methods of dynamic and structural analysis. The results showed a steady seasonal concentration of crime registration in the autumn-winter period (October–February), which accounts for 73.6% of all identified cases, with a systematic minimum in April–June. At the same time, a downward trend in annual indicators was established (a decrease of 50.93% over the study period), which indicates the complex impact of both actual criminal activity and the intensity of control measures. It is confirmed that law enforcement statistics reflect the interaction of "violation intensity" and "control intensity". The scientific novelty of the work lies in the integration of criminal law and statistical analysis, taking into account managerial factors. The practical significance lies in the possibility of using the findings in the planning of operational and preventive measures and the formation of a seasonally oriented model of countering illegal hunting. The study contributes to the development of criminological characteristics of environmental crimes and expands the understanding of the mechanisms of their detection in conditions of seasonal variability.